POLA HUBUNGAN ANTARA PETANI KELAPA SAWIT DENGAN TAUKE SAWIT DI DESA BUANA MAKMUR KECAMATAN DAYUN KABUPATEN SIAK - Ahmadi, Azis; ", Yonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
At first the relationship between palm oil farmers with palm oil tauke only limited economic relations, such as buying and selling relationship between seller and buyer. But in its development, the relationship turned into a social relationship between them. Based on the indicate and phenomena such as well thought above, the writer is interested in conducting research on the Relationship Between Pattern Palm oil farmer With Palm oil tauke in Buana Makmur village subdistrict Dayun in Siak regency. The purpose of this study was to determine the relationship patterns, as well as the background relationship between palm oil farmer with palm oil tauke. The method used in this research is descriptive quantitative method. Descriptive quantitative research is research that aims to explain the phenomenon that is performed using the figures. Sampling method in this study using proposive sampling techniques, this technique aims to determine the sample with a certain considerations. Based on the results of the study, the pattern of the relationship between palm oil farmers and palm oil tauke like buying and selling, accounts payable, social visit, and cooperation. The existence of this background relationship of kinship and attachment althought in accounts payable as wel as sosial interaction between palm oil farmer and palm oil tauke.Keywords: Pattern Relationships, Kinship, Social Interaction